Pengaruh Motivasi Dan Persepsi Terhadap Minat Asn Dalam Pengembangan Karir Fungsional Pengelolaan Pengadaan Barang Dan Jasa Di Pemerintah Kabupaten Kebumen - Jatmiko Jatmiko (SMARTINDO, 2023)
The purpose of this study was to analyze 1) The effect of motivation on ASN's interest in developing a functional career manager of goods and services in the Regional Government of Kebumen Regency 2) The influence of perceptions on ASN's interest in developing a functional career of managing goods and services in the Regional Government of Kebumen Regency. This study uses a quantitative approach. The population in this study is ASN in the Kebumen District Government Office. The research sample wastaken using a purposive sampling technique, namely civil servants who have procurement competency certificates. Data collection using a questionnaire. Data analysis used multiple linear regression analysis techniques. The results of the study can be concluded that: 1) Simultaneously there is a positive and significant influence between motivation and perceptions of ASN's interest in developing a functional career manager of goods and services in the Regional Government of Kebumen Regency; 2) Partially, motivation has a positive and significant effect on ASN's interest in developing a functional career as a manager of goods and services. This means that the higher the motivation, the interest in ASN will increase; 3) Partially, perception has a positive and significant effect on ASN's interest in developing a functional career as a manager of goods and services. This means that the betterthe perception, the interest in ASN will increase.